The effect of cations on reversibility and thermodynamic stability during thermal denaturation of lysozyme. (March 2018) - Stavropoulos, Polychronis; Thanassoulas, Angelos; Nounesis, George
Highlights: Cations affect thermodynamic stability and reversibility of lysozyme. Balance of competing stabilizing and destabilizing electrostatic interactions. Cations change the ability of water molecules to interact with the protein. Abstract: Differential scanning calorimetry (DSC) has been used to investigate the role that cations of different salts (CaCl2, MgCl2, NH4 Cl, NaCl and KCl) play on the thermodynamic stability and reversibility of the lysozyme's folding-unfolding process. In this work, thermodynamic parameters such as enthalpy change ΔΗ, apparent heat capacity change (ΔCp ) and the melt transition temperature (Tm ) were obtained in order to explore the effects of various cations on the thermodynamic stability and thermostability of lysozyme, reflected on the Gibbs free energy change and the melting temperature of the transition. Furthermore, the reversibility index (RI) has been calculated in order to study the reversibility of the process and the effect of cations on protein aggregation. Under all conditions studied, lysozyme undergoes reversible thermal unfolding that can be well represented by a reaction of the form N ⇌ U indicating that the unfolding is a two-state process for the first and the second heating runs that have been used in current experimental analysis. The results of those experiments clearly show that cations destabilize the lysozyme and increase the reversibility of the unfolding process.